Impact of loss-to-follow-up on cancer survival estimates for small populations: a simulation study using Hospital-Based Cancer Registries in Japan - Matthew Barclay; Cong Chen; Ayako Okuyama; Takahiro Higashi (BMJ Open)
Objectives The accuracy of the ascertainment of vital status impacts the validity of cancer survival. This study assesses the potential impact of loss-to-follow-up on survival in Japan, both nationally and in the samples seen at individual hospitals.Design Simulation studySetting and participants Data of patients diagnosed in 2007, provided by the Hospital-Based Cancer Registries of 177 hospitals throughout Japan.Primary and secondary outcome measures We performed simulations for each cancer site, for sample sizes of 100, 1000 and 8000 patients, and for loss-to-follow-up ranging from 1% to 5%. We estimated the average bias and the variation in bias in survival due to loss-to-follow-up.Results The expected bias was not associated with the sample size (with 5% loss-to-follow-up, about 2.1% for the cohort including all cancers), but a smaller sample size led to more variable bias. Sample sizes of around 100 patients, as may be seen at individual hospitals, had very variable bias: with 5% loss-to-follow-up for all cancers, 25% of samples had a bias of <1.02% and 25% of samples had a bias of > 3.06%.Conclusion Survival should be interpreted with caution when loss-to-follow-up is a concern, especially for poor-prognosis cancers and for small-area estimates.